Botanical discrimination and classification of Mentha plants applying two-chiral column tandem GC–MS analysis of eight menthol enantiomers. (December 2022) - Tian, Yu; Xu, Zhigang; Liu, Zhimin; Zhu, Ruizhi; Zhang, Fengmei; Liu, Zhihua; Si, Xiaoxi
Graphical abstract: Highlights: Two-chiral capillary column tandem method used for 8 menthol enantiomers separation. Menthol enantiomers can be used to discriminate natural and synthetic menthol products. Mentha plants were discriminated on a molecular level. The method could be used for quality control and source identification of menthol. Abstract: The concentration and distribution of menthol enantiomers have great significance in discriminating natural mint varieties and evaluating the origin of foodstuffs containing menthol additives. However, the chiral separation of eight chiral menthol enantiomers in Mentha plants offers an easy approach to eliminating or reducing the identification technology problem. The application of derivatized β-cyclodextrin capillary chiral column coupled with derivatized γ-cyclodextrin capillary chiral column, and gas chromatography–mass spectrometry (GC–MS) technology, to isolate and analyze eight chiral menthol enantiomers in 23 natural Mentha plants was investigated. The results showed that the two-chiral columns tandem technology enabled the baseline separation of the eight menthol enantiomers. Four different menthol compounds were only detected in seven out of the 23 natural mint plants. (1R, 3R, 4S)-(−)-menthol and (1R, 3S, 4S)-(+)-neomenthol were detected in the seven mint plant samples, while (1S, 3S, 4R)-(+)-menthol and (1S, 3R, 4R)-(−)-neomenthol could not be detected in the seven mint plant samples. For the two enantiomer couples of (+/−)-isomenthol and (+/−)-neoisomenthol, only (+)-isomers were detected in field mint, candy mint, and peppermint. The Mentha plant samples were distinguished and identified by principal component analysis and radar chart statistical analysis based on the data of the menthol content and isomer ratio. Furthermore, the presence or absence of (1S, 3S, 4R)-(+)-menthol in the samples can be used as an identification factor for discriminating between synthetic menthol and natural sources of menthol.